Tinjauan Hukum Pidana Islam terhadap Tindakan Tidak Melaporkan Transaksi Narkotika - Hanifa Putri, Yasmin; Nasution, Zulkarnain (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, reporting narcotics transactions is a moral and legal obligation to maintain the safety and welfare of the community. However, in practice, many individuals fail to report such actions, creating gaps in law enforcement and community protection efforts. The purpose of this study is to analyze the Islamic Criminal Law perspective on the failure to report narcotics transactions and assess the extent to which Islamic principles such as Maṣlaḥah Mursalah, Amar Ma'ruf Nahi Munkar, and Islamic ethics and morality are applicable. The research methodology employed is a qualitative approach with library research and normative analysis. The study finds that the failure to report narcotics transactions contradicts the principle of Maṣlaḥah Mursalah, which prioritizes public interest and community safety. Additionally, such actions violate the principle of Amar Ma'ruf Nahi Munkar, which calls for the prevention of wrongdoing. The research also reveals that this non-compliance is inconsistent with Islamic ethics and morality, which emphasize individual responsibility in promoting the common good and protecting the community from harm.